An initial estimation of the concentrations of methane (CH4) emitted from the Wakkerstroom wetland and Majuba power station in Mpumalanga province, South Africa - Bobo, Christine (University of the Witwatersrand, Johannesburg, 2024)
The continuous increase in methane (CH4) emissions to the atmosphere poses a formidable challenge to Earth's climate resilience and exacerbates the impacts of global warming. This study compared microbial CH4 concentrations from the Wakkerstroom wetland to fossil fuel concentrations from the coal stockpiles at the Majuba power station in Mpumalanga, South Africa, using three methodological approaches: flexfoil bags, isotopic analysis, and satellite data. Seasonal ground measurements were collected in 3L flexfoil bags and analysed for CH4 mole fraction using a Picarro 2301 calibrated to the WMO X2004A CH4 scale. Samples were prepared for isotopic analysis by continuous-flow isotope-ratio mass spectrometry using an Isoprime Trace Gas system. Findings from ground sampling measurements showed that for three out of the four seasons, Phragmites australis at the Wakkerstroom wetland had the highest CH4 concentration [spring (0.209 ± 0.076 ppm), autumn (0.537 ± 0.239 ppm), and winter (0.132 ± 0.065 ppm)], and the coal stockpiles at the Majuba power station had the lowest CH4 concentration [summer (0.022 ± 0.021 ppm), autumn (0.014 ± 0.053 ppm), and winter (0.002 ± 0.004)]. Isotopic measurements, which identify and differentiate gas sources by examining distinct isotopic signatures, showed that the Wakkerstroom wetland had consistently light, 13C depleted isotopic signatures seasonally ranging between -61.4‰ to -55.6‰. In contrast to this, the Majuba power station coal stockpiles had inconsistent isotopic signatures through the sampling seasons- heavier CH4 emission isotopic signatures with 13C enrichment during spring and summer at -35.3 ± 1.0 ‰ and -43.5 ± 3.5 ‰ respectively, and lighter isotopic signatures with 13C depletion during autumn and winter of - 62.0 ± 1.6 ‰ and - 87.0 ± 10.3 ‰ respectively. On a larger temporal and spatial scale, satellite-based measurements from the Tropospheric Monitoring Instrument (TROPOMI) showed no significant differences between Wakkerstroom (1855.4 ± 18.0 ppb) and Majuba power station (1857.1 ± 22.9 ppb) in terms of the total column averaged dry-air mole fraction of methane (XCH4). An increasing trend in CH4 mole fraction, in Southern Africa as measured at Cape Point Global Atmospheric Watch (GAW) station over a 39-year period was also observed. Meteorological variables, particularly wind direction, had a more significant impact on CH4 mole fractions at Cape Point than at the Wakkerstroom wetland. The multi-faceted approach of utilizing the three measurement techniques provided a comprehensive view of atmospheric CH4 showing that wetlands could be more significant CH4 hotspots in comparison to coal stockpiles at power stations. Measuring methane concentrations is challenging due to its inherent complexity, thus the utilisation of different measurement methodologies further highlighted the spatial and temporal variability of CH4 concentrations at both the wetland and the coal stockpiles.
A dissertation submitted in fulfilment of the requirements for the Degree Master of Science, to the Faculty of Science, School of Animal, Plant and Environmental Sciences, University of the Witwatersrand, Johannesburg, 2024.
Keywords: Methane; Wetland; Coal stockpiles; Source isotopic signature; TROPOMI; GAW; UCTD; SDG-13: Climate action; SDG-15: Life on land